Time-delayed bilateral teleoperation of an aerial manipulator - Coelho, André Fialho (2019)
This thesis presents a framework to allow stable and performant aerial telemanipulation with fully-actuated aerial manipulators. In order to fulfill this objective a time-domain passivity-based controller was applied to cope with the sources of instability introduced by the communication channel, namely time delay, package loss, and jitter. Additionally, in order to improve the position synchronization characteristics of the teleoperation system, a Time Domain Passivity Approach (TDPA) based drift compensator was developed, which, in addition to compensating the drift caused by the passivity controller, ensures that the teleoperation forces remain within a safe range. The drift-compensation approach was also extended to allow its application to multi-DoF robots, including the DLR Suspended Aerial Manipulator (SAM). The efficacy of the proposed drift compensator was demonstrated through simulations and hardware experiments. Adding to that, due to the redundancy of such systems, a whole-body control framework was applied in order to allow the human operator to command Cartesian end-effector poses while a secondary task is autonomously fulfilled in the null space without disturbing the teleoperation system. Numerical validation was performed in order to demonstrate the applicability of the proposed framework to time-delayed aerial telemanipulation scenarios.